2019
DOI: 10.1002/jcp.29041
|View full text |Cite
|
Sign up to set email alerts
|

Brivanib, a multitargeted small‐molecule tyrosine kinase inhibitor, suppresses laser‐induced CNV in a mouse model of neovascular AMD

Abstract: In age-related macular degeneration (AMD), choroidal neovascularization (CNV), a major pathologic feature of neovascular AMD (nAMD), affects 10% of patients, potentially causing serious complications, including vision loss. Vascular endothelial growth factor receptor 2 (VEGFR2) and fibroblast growth factor receptor 1 (FGFR1) contribute to the pathogenesis of CNV. Brivanib is an oral selective dual receptor tyrosine kinase (RTK) inhibitor of FGFRs and VEGFRs, especially VEGFR2 and FGFR1.In this study, brivanib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Similarly, Li et al [ 56 ] showed the same effects in embryonic zebrafish angiogenesis using brivanib, an inhibitor of FGFR and VEGFR. They also used embryos expressing mCherry under the control of the VEGFR2 promotor (endothelial cells expressing mCherry).…”
Section: In Vivo Models Of Neovascular Amdmentioning
confidence: 82%
“…Similarly, Li et al [ 56 ] showed the same effects in embryonic zebrafish angiogenesis using brivanib, an inhibitor of FGFR and VEGFR. They also used embryos expressing mCherry under the control of the VEGFR2 promotor (endothelial cells expressing mCherry).…”
Section: In Vivo Models Of Neovascular Amdmentioning
confidence: 82%
“…These results suggest that levotinib can inhibit the high expression of VEGF in CNV. The investigation by Li et al ( Li et al, 2020 ) showed that tyrosine kinase inhibitors may inhibit angiogenesis of endometrial tissue in the peritoneum by inhibiting the expression of VEGF-A and HIF-1a ( Li et al, 2020 ). It is almost consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…e study was performed according to the local institutional laws and the Chinese law for the Protection of Animals. We followed the methods of Li et al [16]. e following transgenic zebrafish types were used: Tg (Flk:mcherry: Hb9:EGFP), which expresses mCherry (red fluorescence) under the control of Flk (also termed vascular endothelial growth factor receptor 2, a vascular endothelial cell marker) and EGFP (green fluorescence) under the control of Hb9 (also termed motor neuron and pancreas homeobox 1, a differentiated motor neuron marker), and Tg (Flk:EGFP), which expresses EGFP (green fluorescence) under the control of the regulatory sequences of Flk.…”
Section: Zebrafish and Drug Treatmentmentioning
confidence: 99%
“…VEGFR2 and alleviates the leakage, lesion area, and formation of CNV via intravitreal injection or oral gavage [16].…”
Section: Journal Of Ophthalmologymentioning
confidence: 99%